2020
DOI: 10.1093/tbm/ibaa110
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics associated with changes in food security status among college students during the COVID-19 pandemic

Abstract: The prevalence of food insecurity in the USA has increased since the start of the COVID-19 pandemic; however, past studies have not examined how the food security status of college students has been impacted. The purpose of this study was to examine changes in the prevalence of food insecurity; determine the proportion of students experiencing a change in food security status; and identify characteristics associated with changes in food security status from before to during the COVID-19 pandemic among a sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 11 publications
6
80
3
Order By: Relevance
“…This finding supports prior findings on food insecurity during the COVID-19 pandemic ( Karpman et al, 2020a ). In contrast, race was not associated with food insecurity in either study, conflicting previous findings that people of color tend to be at a greater risk of food insecurity during the COVID-19 pandemic ( Karpman et al, 2020a , Karpman et al, 2020b , Owens et al, 2020 , Schanzenbach and Pitts, 2020 , Waxman et al, 2020 , Wolfson and Leung, 2020 ) and after controlling for socioeconomic status ( Myers and Painter, 2017 , Soldavini et al, 2021 ). This surprising finding may be due to the overshadowing effect of financial struggles as a large predictor of food insecurity.…”
Section: Discussioncontrasting
confidence: 90%
“…This finding supports prior findings on food insecurity during the COVID-19 pandemic ( Karpman et al, 2020a ). In contrast, race was not associated with food insecurity in either study, conflicting previous findings that people of color tend to be at a greater risk of food insecurity during the COVID-19 pandemic ( Karpman et al, 2020a , Karpman et al, 2020b , Owens et al, 2020 , Schanzenbach and Pitts, 2020 , Waxman et al, 2020 , Wolfson and Leung, 2020 ) and after controlling for socioeconomic status ( Myers and Painter, 2017 , Soldavini et al, 2021 ). This surprising finding may be due to the overshadowing effect of financial struggles as a large predictor of food insecurity.…”
Section: Discussioncontrasting
confidence: 90%
“…A basic needs report of the California State University system estimated that 22·4 % of the student body is marginally food secure (1) , defined as having ‘…problems at times, or anxiety about, accessing adequate food, but the quality, variety and quantity of their food intake were not substantially reduced’ (2) . Since the beginning of the COVID-19 pandemic, some studies have indicated that food security has decreased by as much as a third among college students (3,4) . Recently, research has found positive associations between marginal food security and depression, BMI, less cooking and food agency, worse perceived health and lower grade point averages among college students (5–7) .…”
mentioning
confidence: 99%
“…The nutritional response to the pandemic has been quite different in Europe and North America. In the US, the prevalence of food insecurity increased by one third from before to during the pandemic [ 54 , 55 ]. Even in the USA, disadvantaged communities have shown signs of severe food insecurity during the COVID-19 pandemic [ 56 ].…”
Section: Food Security In the Covid-19 Pandemicmentioning
confidence: 99%
“…Even in the USA, disadvantaged communities have shown signs of severe food insecurity during the COVID-19 pandemic [ 56 ]. This appears to have been experienced across a wide age range of adults, from college students to the elderly [ 54 ].…”
Section: Food Security In the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation